ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN FREKUENSI KUNJUNGAN ANTENATAL CARE (ANC) DI PUSKESMAS LINGGA KABUPATEN KUBU RAYA KALIMANTAN BARAT TAHUN 2014 - ., Nur Annisa (Universitas Tanjungpura, 2015)
Mother mortality is one of serious problems faced by many countries, including Indonesia. Therefore,government of Indonesia made a health program that one of its pillars is antenatal care, whichpurposed to reduce mortality and complication during pregnancy.The aim of this study is toinvestigate the correlation between knowledge level, husband